Pemanfaatan Zakat untuk Pemulihan Ekonomi Pasca Pandemi Covid-19 - Ibrahim, Muhammad Yusuf; Lubis, Rusdi Hamka (Al-Tasyree: Jurnal Bisnis, Keuangan dan Ekonomi Syariah, 2021)
The research is aim to analyze the effect of the zakat instrument on poverty and unemployment and test the zakat instrument as an alternative solution to the economic impact of the middle to lower class post-pandemic community. It uses least square regression as the method of analysis. Where the method is in line with the research objectives that is to test the form of the relationship and the level of significance of the effect of the observed variable. Findings show that H01 is rejected and H11 is accepted, or the zakat instrument has a negative relationship with the poverty and unemployment instrument. As well as the zakat instrument also has a significant effect on the poverty and unemployment instrument or H12 accepted. This research is limited to the geography of Indonesian research. By taking secondary data from reliable sources related to research topics, such as the Baznaz and BPS websites. The time interval for data in this study was taken from 2002 to 2019. Developed from Beik & Arsyanti (2016) published in the journal of Islamic monetary economics and finance 1 (2) pages 141-160 with the title Measuring Zakat Impact on Poverty and Welfare using the Cibest Model. And current research will review with empirical evidence through secondary data about the effectiveness of the zakat instrument in overcoming economic problems in the middle to lower society, especially regarding poverty and unemployment. This aims to strengthen the reasons for submitting zakat instruments to be applied as an alternative solution for post-pandemic economic restoration tools. By taking case simulations from previous crises and testing their effects in the long run. Therefore, in the current research, the method that will be applied is least square regression. Because it is in accordance with the objectives and research conditions at this time. It is a form of refinement on previous research and development with the latest economic cases.